Dictatorship Of Fast-Running Time Within The Society Of Experience - Roubal, Ondřej (Communication Today, 2025)
The circumstances of transition of the society of deficit into the society of welfare have been a subject of intense sociological studies. The society of material abundance creates specific life conditions, increasingly focused on non-material values and subjective experience. In this relation, we talk about the concept of the society of experience, where the main drive of many human activities lies in the search for experience and increasingly more intense need for experiencing the own physical. The society of experience advocates a pleasure-seeking lifestyle; experience thus becomes a target of immediate satisfaction. Preferring instant gratification has to do with an explosion of offers related to all types of entertainment and experience as well as with the onset of an information era which has introduced an unprecedentedly fast-running time into the human life.